Synthesis and homopolymerization kinetics of 7-(methacroyloxy)-2-oxo-heptylphosphonic acid and its copolymerization with methyl methacrylate - Štefan Chmela; Agnesa Fiedlerová; Tibor Liptaj; Yohann Catel; Norbert Moszner (Designed Monomers and Polymers, 2019)
The synthesis of polymerizable 7-(methacroyloxy)-2-oxo-heptylphosphonic acid M1 destined for self-etch adhesives is described. M1 is characterized by 1H, 13C and 31P-NMR spectroscopy. Its homopolymerization and copolymerization reactivity in the solvents methanol and dioxane between 45 and 70°C in the presence of azobisisobutyronitrile (AIBN) are examined. Polymerization proceeds readily through a thermal free radical initiation. The intensity exponents for the monomer and initiator are only slightly over 1 and approximately 0.5, respectively. This is in accordance with the results typically observed for an ideal free radical polymerization with termination mainly by disproportionation, which is typical for methyl methacrylate (MMA) homopolymerization. The kinetics of copolymerization with MMA are monitored by online 1H-NMR spectroscopy. Two copolymerization reactions for each pair of co-monomers are sufficient to evaluate the copolymerization parameters using the Jaacks method, the Fineman–Ross method and the nonlinear least-squares method. All three methods give similar results for particular monomer M1/MMA couple.